Step * 2 2 1 of Lemma unsat-omega_step

.....antecedent..... 
1. : ℕ
2. eqs {L:ℤ List| ||L|| (n 1) ∈ ℤ}  List
3. ¬(eqs [] ∈ ({L:ℤ List| ||L|| (n 1) ∈ ℤ}  List))
4. ineqs {L:ℤ List| ||L|| (n 1) ∈ ℤ}  List
5. ¬if eqs Ax then if ineqs Ax then otherwise ||hd(ineqs)|| otherwise ||hd(eqs)|| 1 < 1
6. ¬(n 0 ∈ ℤ)
7. xs : ℤ List
8. x1 (∀as∈eqs.xs ⋅ as =0)
9. x2 (∀bs∈ineqs.xs ⋅ bs ≥0)
10. first-success(λL.find-exact-eq-constraint(L);eqs) ∈ i:ℕ||eqs||
    × x:{x:ℤ List| eqs[i] ∈ (ℤ List)} 
    × {i@0:ℕ+||eqs[i]||| |eqs[i][i@0]| 1 ∈ ℤ?
11. 0 ∈ ℤ
12. first-success(λL.find-exact-eq-constraint(L);eqs)
(inr Ax )
∈ (i:ℕ||eqs|| × x:{x:ℤ List| eqs[i] ∈ (ℤ List)}  × {i@0:ℕ+||eqs[i]||| |eqs[i][i@0]| 1 ∈ ℤ?)
⊢ satisfies-integer-problem(eqs;ineqs;xs)
BY
xxx(D THEN Auto)xxx }


Latex:


Latex:
.....antecedent..... 
1.  n  :  \mBbbN{}
2.  eqs  :  \{L:\mBbbZ{}  List|  ||L||  =  (n  +  1)\}    List
3.  \mneg{}(eqs  =  [])
4.  ineqs  :  \{L:\mBbbZ{}  List|  ||L||  =  (n  +  1)\}    List
5.  \mneg{}if  eqs  =  Ax  then  if  ineqs  =  Ax  then  0  otherwise  ||hd(ineqs)||  -  1  otherwise  ||hd(eqs)||  -  1  <  1
6.  \mneg{}(n  =  0)
7.  xs  :  \mBbbZ{}  List
8.  x1  :  (\mforall{}as\mmember{}eqs.xs  \mcdot{}  as  =0)
9.  x2  :  (\mforall{}bs\mmember{}ineqs.xs  \mcdot{}  bs  \mgeq{}0)
10.  first-success(\mlambda{}L.find-exact-eq-constraint(L);eqs)  \mmember{}  i:\mBbbN{}||eqs||
        \mtimes{}  x:\{x:\mBbbZ{}  List|  x  =  eqs[i]\} 
        \mtimes{}  \{i@0:\mBbbN{}\msupplus{}||eqs[i]|||  |eqs[i][i@0]|  =  1\}  ?
11.  y  :  0  =  0
12.  first-success(\mlambda{}L.find-exact-eq-constraint(L);eqs)  =  (inr  Ax  )
\mvdash{}  satisfies-integer-problem(eqs;ineqs;xs)


By


Latex:
xxx(D  0  THEN  Auto)xxx




Home Index